Mucîruddîn el-Uleymî (öl. 928/1522) ve Fethu'r-Rahmân fî Tefsiri'l-Kur'ân Adlı Tefsiri - Doğan, İshak (Muş Alparslan Üniversitesi, 2021)
In this study, the life of Mujiruddin al-Ulaymî, known as the “Qad of Jerusalem”, who is also a historian and mufassir, and his method in his commentary called Fethu’r-Rahmân fî Tafsiri’l-Qur’an, which has come to light in recent years, are examined. The interpretation of Uleymi, who lived in Jerusalem, a holy city for three major religions and served as a judge until the end of his life. His views on Qur’anic sciences such as Mekki-Medenî, nâsih-mensûh, muhkam-mutasabih, garîbu’l-Qur’an and mecâzu’l-Qur’an were also expressed in addition to the method he put forward in his interpretation in terms of narration and acumen, language and eloquence. Fethu'r-Rahmân, one of the few Hanbali commentators who have survived to this day, is important in terms of reflecting the understanding of the Qur'an at a time when the Mamluk State ended and the Ottoman Empire dominated Jerusalem. This tafseer (exegesis), written in a geography where many sects are based in Jerusalem and dominated by Jewish culture, can give signs of a simple and easy-to-understand exegesis writing that unites different segments, especially without highlighting sectarian loyalties today.

Bu çalışmada ‘Kudüs kadısı’ olarak bilinen, aynı zamanda bir tarihçi ve müfessir olan Muciruddin el-Uleymî’nin hayatı ve son yıllarda gün yüzüne çıkmış olan Fethu’r-Rahmân fî Tefsiri’l-Kur’ân adlı tefsirindeki metodu incelenmiştir. Üç büyük dinin kutsal kabul ettiği Kudüs şehrinde yaşayan ve ömrünün sonuna kadar kadılık görevinde bulunan el-Uleymî’nin tefsiri, ahkâm ve kıraatle ilgili konulara verdiği önemle öne çıkar. Çalışmada onun rivayet, dirayet, dil ve belağat açısından ortaya koymuş olduğu metodun yanı sıra Mekkî-Medenî, nâsih-mensûh, muhkem-müteşâbih, garîbu’l-Kur’ân ve mecâzu’l-Kur’ân gibi Kur’ân ilimleri hakkındaki görüşleri de incelenmiştir. Günümüze ulaşan az sayıdaki Hanbelî müfessirlere ait tefsirlerden biri olan Fethu’r-Rahmân, Memlûk Devleti’nin son bulduğu ve Osmanlı Devleti’nin Kudüs’e hâkim olduğu bir dönemin Kur’ân anlayışını yansıtması açısından önem arz etmektedir. Birçok mezhebin Kudüs’te yerleşik durumda bulunduğu ve Yahudi kültürünün hâkim olduğu bir coğrafyada yazmış olduğu bu tefsir, günümüzde özellikle mezhebî bağlılıkların öne çıkarılmadan, farklı kesimleri birleştirici, halk için sade ve kolay anlaşılır bir tefsir yazımı konusunda işaretler verebilir.
Mujiruddin al-Ulaymi (d. 928/1522) and His Tafseer ‘Fethu’r-Rahman fî Tefsiri’l-Kur’ân’
dinbil
Keywords: Tafseer; Mujiruddin al-Ulaymî; Fethu’r-Rahmân; Isra’iliyyat; Jerusalem; Tefsir; Muciruddin el-Uleymî; Fethu’r-Rahmân; İsrailiyyat; Kudüs